2017
DOI: 10.12681/bgsg.14268
|View full text |Cite
|
Sign up to set email alerts
|

Organic Pollutants in the Groundwaters Used for Irrigation Purpose Within a Coal-Bearing Basin of Northern Greece

Abstract: The aim of this study is to identify potential toxic or environmentally relevant organic compounds in the aquifers of the Amynteo hydrogeological basin and to investigate a possible link of the identified organic contaminants with the Περίληψη Σκοπός της παρούσας μελέτης είναι ο εντοπισμός τοξικών οργανικών ενώσεων στα υπόγεια ύδατα της υδρογεωλογικής λεκάνης Αμυνταίου και η έρευνα μιας πιθανής σύνδεσης αυτών των οργανικών ρυπαντών με τους λιγνίτες της περιοχής. Δέκα δείγματα υπόγειων υδάτων συλλέχθηκαν και υπ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…In contrast, water samples taken from Afşin-Elbistan area are not contaminated with these abovementioned nephrotoxic and carcinogenic organic compounds, which may suggest a minimal influence of coal deposits on the groundwater quality. This outcome is parallel to the results of Iordanidis et al (2016) and Kosateva et al (2017a) reported. PAHs were not found in Amyneto lignites, Northern Greece and similarly coal derived PAHs were also not found in groundwater samples taken from Amyneto lignite basin which in turn indicates a minor influence of lignite deposits on groundwaters (Iordanidis et al, 2016).…”
Section: Organic Analysessupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, water samples taken from Afşin-Elbistan area are not contaminated with these abovementioned nephrotoxic and carcinogenic organic compounds, which may suggest a minimal influence of coal deposits on the groundwater quality. This outcome is parallel to the results of Iordanidis et al (2016) and Kosateva et al (2017a) reported. PAHs were not found in Amyneto lignites, Northern Greece and similarly coal derived PAHs were also not found in groundwater samples taken from Amyneto lignite basin which in turn indicates a minor influence of lignite deposits on groundwaters (Iordanidis et al, 2016).…”
Section: Organic Analysessupporting
confidence: 89%
“…This outcome is parallel to the results of Iordanidis et al (2016) and Kosateva et al (2017a) reported. PAHs were not found in Amyneto lignites, Northern Greece and similarly coal derived PAHs were also not found in groundwater samples taken from Amyneto lignite basin which in turn indicates a minor influence of lignite deposits on groundwaters (Iordanidis et al, 2016). In other studies, Kosateva et al (2017a) did leach experiments on Bulgarian lignites for 10 weeks by using different solvents and analytical equipments however did not find any harmful/ toxic organic compounds in the leachates (Kosateva et al, 2017a;2017b).…”
Section: Organic Analysessupporting
confidence: 89%